Oncogenic transformation-dependent expression of a transcription factor NF-Y subunit - Gu, Zhennan; Rommelaere, Jean (Molecular carcinogenesis, 1999)
As a result of differential splicing, one subunit of the nuclear factor Y (NF-Y) consists of two major isoforms designated short (NF-YaS) and long (NF-YaL). In proliferating normal human fibroblasts, NF-YaL is by far the more expressed isoform. Surprisingly, NF-YaS was found by immunoblotting to be as prominent as NF-YaL in simian virus 40 (SV40)-transformed cell derivatives. As a consequence, two NF-Y/DNA complexes, one containing the long and the other the short isoform, were formed with extracts from transformed cells and a target promoter element in electrophoretic mobility-shift assays. Only the complex containing NF-YaL was detected with extracts from normal fibroblasts. Furthermore, the NF-Y recognition motif contributed to promoter activation in SV40-transformed cells but not in normal, cells. Our finding links transcription stimulation in transformed cells to quantitative changes in the expression of an NF-Ya subunit.
Gesehen am 11.02.2021